Karamah dan Rabitah Mursyid dalam Perspektif Tarekat Naqsyandiyah - Faisal Muhammad Nur (Jurnal Pemikiran Islam, 2021)
Karamah for the murshid of the tarekat serves to glorify the lovers of Allah, and to support them in preaching according to the guidance of Islamic Shari'a, because the karamah comes from the miracles of the Prophet Muhammad. The purpose of this study is to find out the forms of karamah of the murshid of the tarekat and their practice in the naqsyabandiyah tarekat. As a qualitative research, researchers collect data through literature review to find the data needed for research purposes. The results of the study show that with the appearance of karamah in murshid, it becomes a glory because of their faith and sincerity in implementing Islamic Shari'a perfectly. The practice of rabitah murshid in the Naqshbandiyah congregation is under the guidance of Islamic Shari'a and is not classified as shirk, because of the beliefs of the followers of the Naqshbandiyah congregation do not have any authority in carrying out all their activities but are based on the provisions of Allah SWT. Those provisions are what they call karamah, and karamah is based on the will of Allah.AbstrakKaramah bagi para mursyid tarekat berfungsi untuk memualiakan para kekasih Allah Swt, serta untuk mendukung mereka dalam berdakwah sesuai dengan tuntunan Syariat Islam, sebab karamah itu bersumber dari mu’jizat Nabi Muhammad Saw. Tujuan penelitian ini ingin mengetahui bentuk-bentuk karamah para mursyid tarekat dan pengamalan mereka dalam tarekat naqsyabandiyah. Sebagai penelitian kualitatif, peneliti mengumpulkan data melalui penelusuran kepustakaan guna menemukan data-data yang dibutuhkan untuk keperluan penelitian. Adapun hasil penelitian yang didapatkan bahwa dengan munculnya karamah pada diri para mursyid menjadi kemuliaan dikarenakan keimanan serta keihklasan mereka dalam menjalankan Syariát Islam secara sempurna. Pengamalan rabitah mursyid dalam tarekat naqsyabandiyah sesuai dengan tuntunan syariát Islam dan tidak tergolong dalam perbuatan syirik, sebab keyakinan para penganut tarekat naqsyabandiyah tidak memiliki otoritas apapun dalam melakukan segala aktifitas mereka melainkan berdasarkan pada ketentuan Allah Swt. Ketentuan itu yang mereka namakan dengan karamah, dan karamah itu terjadi berdasarkan kehendak Allah Swt.